Heterogeneity of NK Cells and Other Innate Lymphoid Cells in Human and Murine Decidua - Vacca, Paola; Chiossone, Laura; Mingari, Maria Cristina; Moretta, Lorenzo (Frontiers in Immunology, 2019)
Innate lymphoid cells (ILCs) represent a heterogeneous group of cells lacking genetically rearranged antigen receptors that derive from common lymphoid progenitors. Five major groups of ILCs have been defined based on their cytokine production pattern and developmental transcription factor requirements; namely, natural killer (NK) cells, ILC1s, ILC2s, ILC3s and lymphoid tissue-inducer (LTi) cells. ILC1s, ILC2s and ILC3s mirror the corresponding T helper subsets (Th1, Th2 and Th17, respectively) and produce cytokines involved in defense against pathogens, lymphoid organogenesis and tissues remodeling. During the first trimester of pregnancy, decidual tissues contain high proportion of decidual NK (dNK) cells, representing up to 50% of decidual lymphocytes, and ILC3s. They release peculiar cytokines and chemokines that contribute to successful pregnancy. Recent studies revealed that ILCs display a high degree of plasticity allowing their prompt adaptation to environmental changes. Decidual NK cells may derive from peripheral blood NK cells migrated when pregnancy establishes or from in situ differentiation of hematopoietic precursors. Previous studies showed that human and murine decidua contain dNK cells, tissue resident NK cells, and ILC3s, all characterized by unique phenotypic and functional properties, most likely induced by decidual microenvironment to favor the establishment and the maintenance of pregnancy. Thus, during the early phase of pregnancy, the simultaneous presence of different ILC subsets further underscores the complexity of the cellular components of decidual tissues as well as the role of decidual microenvironment in shaping the plasticity and function of ILCs.